A Comparison of Goiso Oinan and Masi Dialect In Mentawai Islands - Mac Aditiawarman; Fernando Satepuk (Fakultas Sastra Universitas Ekasakti, 2025)
This This research compares the Goiso Oinan and Masi dialects, which are part of the Mentawai language in the Mentawai Islands. The research aims to analyze the linguistic similarities and differences, particularly in the aspects of phonology, morphology, and lexicon between these two dialects. A qualitative descriptive method was employed, with data collected through direct interviews with native speakers of both dialects in the Goiso Oinan area located in the Sipora Utara District and the Masi area in the Siberut Barat Daya District. The data were analyzed using systematic techniques of data reduction, data presentation, and conclusion drawing. The findings reveal that there are words with similar phonemic forms and meanings in both dialects. However, morphological changes also occur through the addition, deletion, and substitution of phonemes in various word positions. Furthermore, there are dialectal variations with different word forms but the same meanings, reflecting the complexity and dynamic evolution of dialects influenced by geographical, social, and economic factors. The research also found that the Goiso Oinan dialect is the dominant dialect, while the Masi dialect serves as a contributing dialect. Approximately 60 percent of the lexical items share the same forms and meanings, while 40 percent differ in form but retain the same meanings. This study makes a significant contribution to the documentation and preservation of local dialects as part of the cultural heritage of Mentawai, as well as to the development of dialectology and Austronesian linguistics.